High-Ability College Students and Undergraduate Honors Programs: A Systematic Review. (September 2019) - Rinn, Anne N.; Plucker, Jonathan A.
Meeting the intellectual needs of high-ability students does not end upon graduation from high school. However, limited attention is paid to the important topic of postsecondary advanced learning in the research literature. In this systematic review, we identified 52 empirical studies published during the past 15 years. Results suggest various cognitive and psychosocial factors influence achievement among high-ability college students and that honors programming leads to positive student outcomes. The findings are discussed in light of the need for an understanding of high-ability college students and postsecondary honors education.